Penerapan Hak Asasi Manusia dalam Penyidikan Perkara Pidana Pencurian Kendaraan Bermotor di Polrestabes Medan - Cordyn Parulian Tuah Purba; Taufik Siregar; Rizkan Zulyandi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this research is to analyze the application of human rights, the obstacle factors and efforts to overcome them against the suspected perpetrators of motor vehicle theft at the investigation stage at the Medan Police. The research method used is descriptive method, while the data analysis technique uses qualitative. The results of the study indicate that the Medan Police as a law enforcement officer has tried to implement human rights in carrying out investigations into criminal acts of ranmor, and still prioritize the purpose of the investigation, which is to make the case clear and find the suspect. The obstacles faced in the effort to implement human rights for ranmor suspects are: the police must try to fully uncover the ranmor case even with various examination techniques, the intervention of the ranmor victim during the investigation and while in detention, being given lessons in the form of physical violence, and the behavior of the suspect who often does not cooperative during the investigation process so as to force the investigator to conduct an examination using physical force. The efforts that can be made to overcome the obstacles faced in the effort to implement human rights for ranmor suspects are: trying to fully uncover the case without using physical violence, firmly rejecting all forms of intervention from victims of the ranmor crime, and providing understanding for the ranmor suspect on the importance of attitude. cooperatively during the investigation for the purpose of mutual interest.